Writing as Praxis: A Neo-Marxist and Lacanian Understanding of the Creative Writing Process as Representation of Man’s Drive Toward Coherence - Brantley, Anthony Joseph (My University, 2013)
In the following thesis, I am going to examine the creative writing process. And I am going to try and show that as a praxis, it allows for a type of reimagining of one’s relationship to one’s conditions of existence. As I show, writers of imaginative literature have articulated a way of theorizing creative writing that is very similar to the ways in which some classical and neo-Marxists, as well as Lacanian, critics and theorists have done so. By showing the connections among these various schools of thought, I hope to bridge somewhat the gap that has emerged between creative writing studies as a discipline and literary criticism. I truly believe the potential benefits that might result for literary criticism include not only opening-up the discipline to unexplored areas of research, but also strengthening the rigor and integrity of its analytical quality insights.
A Thesis submitted by Anthony Brantley to the Graduate School Valdosta State University in Partial fulfillment of requirements for the degree of MASTER OF ARTS in English
Keywords: Creative Writing; Marxism; Literary Criticism; Praxis; T.S. Elliot; Jacques Lacan (Lacanian); Degree--English